Global experience in attracting investments for the innovative development of construction enterprises - Maksiuta, A. (Ways to Improve Construction Efficiency, 2023)
In the context of globalization and economic uncertainty, the analysis of international experience in developing the investment potential of various countries becomes particularly relevant. The successful practices of developed nations, as well as post-socialist countries where market and economic processes have undergone significant growth, can serve as a valuable benchmark for fostering investment activity in Ukraine. The article examines the global experience in attracting investments to ensure the innovative development of construction enterprises. It is substantiated that the modern global trend in construction development is accompanied by technological innovations that actively influence the socio-economic environment. This trend is characterized by the advantages of innovative factors and conditions impacting the economic position of the construction sector and adapting successful investment stimulation tools to the conditions of Ukraine. Directions of state policy that could enhance investment potential are identified, including improving tax regulation, creating a favorable business climate, and supporting innovative activities. An analysis was conducted of investment support models, their key features, efficiency, and the dynamics of attracting foreign direct investments in Ukraine, as well as an examination of global experience in stimulating the investment activity of enterprises. Based on this experience, recommendations were proposed for adapting advanced practices to domestic conditions, taking into account the specifics of Ukraine's economy and the state of the construction industry. Key directions that promote investment activity in developed countries were identified, including: Tax and depreciation incentives that provide financial advantages for investors; State support, including subsidies, grants, and other facilitation mechanisms; Innovative development focused on implementing modern technologies and enhancing competitiveness. The results of the study emphasize the importance of a comprehensive approach to stimulating investments in Ukraine, considering the specifics of the national economy and the successful experiences of other countries. This will contribute to ensuring sustainable economic development and enhancing the country's competitiveness on the international stage after the cessation of aggression by russia.